ONTOLOGICAL ASPECTS OF CONSTRUCTING E-SCRIPT SUPPORT OF SCIENTIFIC PUPILS RESEARCHES OF MINOR ACADEMY OF SCIENCES OF UKRAINE (Journal of Information Technologies in Education (ITE), 2013)
The approaches, tools and technologies shaping the corporate personalized IT systems forming knowledge are described. The ontological aspects construction of the model is the e-script process scientific pupil’s researches of the Minor academy of sciences of Ukraine are considered with using ICT. This involves solving the urgent problems to increasing the efficiency of pupils research MASU by applying modern network of e-remote access to distributed systems forming knowledge.
Keywords: personalized corporate IT system; research activities of pupils; information sources forming knowledge; ontological model e-script support of the research process